Application of intelligent applications for controlling software and hardware devices - Baftiu, Naim (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This paper will show how to apply the smart application "Smart Drinia Tech" which serves to control software and hardware devices. It will show how to work with this web application, what are the advantages and disadvantages of this application and how much use this application finds in Kosovo. This paper will provide us with general knowledge about the use of the application "Smart Drinia Tech" in computer systems, first the web will be shown and then how to connect to this application. The practical work of this application will also be analyzed, where some pictures of different types of devices that make the distribution of the Internet in local offices or homes, which are controlled and configured through the application "Smart Drinia Tech" will be displayed. This tutorial will help many internet users learn how to control their devices at home without the need for additional costs.